N-ASTHEAL ®, A HERBAL FORMULA FOR THE TREATMENT OF MILD ASTHMA: AN OPEN, SINGLE CENTRIC, NON- COMPARATIVE PILOT STUDY FOR 3 WEEKS - AGARWAL, SHAMBHU; JAIN, ANSHUL; JAIN, ASHISH; MOURYA, MUGIL; KC, VANDANA; P, JACKSON; CHOUDHARY, YOGENDRA KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The aim was to evaluate efficacy and safety of N-Astheal® in a pilot study on 12 patients with mild to moderate bronchial asthma. Materials and Methods: The study was an open-label, single centric clinical trial conducted by Ethix Pharma at Clinical Research Center, CMC & H, Bhaisa Khedi, Bhopal, India from 12 March to 30 May 2013. The study was conducted on 12 patients comprised of 8 male and 4 female with an age range of 18-70 years, all the subjects were with mild to moderate bronchial asthma. Patients with another chronic lung disease (other than asthma) and those who are suffering from breathlessness due to cardiovascular disorders were excluded. Pregnant or lactating females were also excluded in the study. The potential subjects were screened and consented. The consented subjects were enrolled in the study and baseline history was obtained in order to determine the patient's eligibility for enrollment in the trail. Thereafter all patients underwent a clinical examination, including hematology, biochemistry, urinalysis and spirometry test. All patients were advised to take N-Astheal twice in a day for a period of 3 weeks. All patients were followed-up twice after giving N-Astheal and during each follow-up visit, physical examination, vitals examination, spirometry, acoustic emission monitoring was done. The final assessment was carried out for decrease in the severity and symptoms of asthma, improvement of forced expiratory volume in one second (FEV1), improvement in forced vital capacity (FVC) and percentage improvement in peak expiratory flow rate (PEFR). Statistical analysis was performed according to intention-to-treat principles. Results: The overall response to the treatment by N-Astheal® observed a significant reduction in the severity and symptoms of asthma along with significant improvement in FEV1 from 65.2% to 74.9% (*p<0.05), FVC from 96.2% to 105.1% (*p<0.05), PEFR from 44.4% to 64.2% (**p<0.01) was observed from 1st week to 4th week, respectively. This pilot study revealed the beneficial effect of N-Astheal® in acute asthma and similar respiratory condition. Conclusion: The present pilot study 3 weeks treatment of N-Astheal® had been promising in treating asthma and similar respiratory conditions and at the same time the treatment was proved safe as well with a very good patient compliance. Keywords: Asthma, N-Astheal®, inflammation, Anti-asthmatic agent, Clinical